Knowledge-Oriented Leadership and Organizational Performance: Mediating Role of Knowledge Management in the Banking Industry - Chaudhary, Manoj Kumar; Dhungana, Madan; Bohara, Beeja (Nepal Journal of Multidisciplinary Research, 2025)
Background: Effective leadership in managing knowledge resources has become essential for organizational success in today's information-driven and competitive economy. As a knowledge-intensive industry, banking depends on strategically applying knowledge assets to improve operational effectiveness, innovation, and service quality. Consequently, by cultivating a culture that encourages knowledge creation, sharing, and application, Knowledge-Oriented Leadership (KOL) has become a significant performance driver. Objectives: Using the Knowledge-Based View and the Path-Goal Theory, this study investigates how Knowledge-Oriented Leadership affects Organizational Performance in Nepal's banking sector, emphasizing the mediating role of Knowledge Management procedures. Methods: This research adopts a descriptive and causal design, using non-probability convenience sampling from 319 employees of commercial banks in Kathmandu. A structured questionnaire was used to collect data, and regression modeling, correlation analysis, and mediation techniques were used to assess the hypotheses. Results: The results show a strong positive correlation between organizational performance and knowledge-oriented leadership, suggesting collaborative leaders improve performance. Further, mediation analysis demonstrates that this relationship is partially mediated by knowledge management processes, emphasizing both the knowledge-driven and direct effects of leadership on performance. Novelty: This study is among the limited empirical studies in Nepal exploring how KOL drives organizational performance through KM processes. By extending leadership and KM theories into a developing economy context, it offers valuable theoretical and managerial contributions for improving performance in knowledge-intensive industries.